Effects of training with an agility ladder on sprint, agility, and dribbling performance in youth soccer players - Padrón-Cabo, A.; Rey, E.; Kalén, A.; Costa, P. B. (Journal of Human Kinetics, 2020)
The aim of this study was to examine the effects of coordination training using an agility ladder compared with a control group on physical fitness and technical performance in youth soccer players. Eighteen male youth soccer players (age: 12.2 ± 0.4 years; body height: 158.3 ± 10.8 cm; body mass: 45.0 ± 8.0 kg) were randomly assigned to an agility ladder group (n = 10) or a control group (n = 8). The intervention program was carried out three times a week over six weeks. Before and after the training period, the 10 m sprint, 20 m sprint, dribbling speed test, agility test, and slalom dribbling test performances were assessed. Within-group analysis showed significant improvements (p < 0.005) in 10 m and 20 m sprint performance from the pre- to the post-test for the agility ladder group (-2.39% and -2.10%) and the control group (-2.54% and -1.44%). No significant differences (p > 0.005) were found from the pre- to the post-test in the dribbling speed test, agility test, slalom dribbling test, and skill index. In the between-group analysis, there were no differences between the agility ladder group and the control group in any variable. In conclusion, the findings of this study suggest coordination training with an agility ladder does not seem to be effective to improve physical fitness and dribbling. Therefore, this information could be beneficial to players and coaches for programming tasks during soccer training sessions.